Design and control of a single phase synchronous inverter for microgrid - Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn; Rahman, Tawfikur (Science and Engineering Research Support Society, 2019)
Microgrid power system is becoming popular for utilizing renewable energy. This energy should invert to supply AC for microgrid, but inversion of the renewable energy has suffered some issues; inferior quality of waveform, large phase difference, high switching loss and poor power quality. A new scheme of phase synchronous inverter (PSI) has outline in the microgrid system which improve the quality of the power supply. A pulse width modulation (PWM) signal is generated for PSI to precisely synchronize with the grid line frequency. A lowpass LC filter is utilized to reduce the higher harmonics frequency in the inverter. In this research a resistive load of 40 Ω and input DC voltage ± 35 V has been considered. A PWM of 1600 Hz carrier frequency and 95% modulation index with 50 Hz fundamental frequency has been examined in this project. The simulated results show that the proposed PSI overall efficiency is 96%, total harmonic distortion (THD) is 3.9% and phase distortion is about 4 degrees. Therefore, it is highly appreciated that proposed design will improve the microgrid power supply system.